2012
DOI: 10.1210/en.2011-2154
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobindin-2 Is a Positive Modulator of EGF-Dependent Signals Leading to Enhancement of Cell Growth and Suppression of Adipocyte Differentiation

Abstract: Nucleobindin-2 is a 420-amino-acid EF-hand calcium-binding protein that undergoes proteolytic processing to generate an 82-amino-acid amino-terminal peptide termed nesfatin-1. To determine whether nucleobindin-2 has any biological function, nucleobindin-2 was either overexpressed or knocked down by short hairpin RNA in cultured CHO cells expressing the human insulin and epidermal growth factor (EGF) receptors (CHO/IE) and in 3T3-L1 cells. Reduction in nucleobindin-2 expression inhibited EGF-stimulated MAPK kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
3
13
0
1
Order By: Relevance
“…Recently, in vitro experiments using a neural cell line demonstrated that nesfatin-1 stimulates the phosphorylation of MAPK (19), CREBP (20), and AMPK (11), playing important roles in regulating feeding behavior and energy metabolism in vivo (12,13,(16)(17)(18)22,23). Our in vivo finding that the ICV injection of nesfatin-1 concentration dependently increased MAPK activity (phosphorylation of ERK1/2), but not AMPK, PI3K, or CREBP activity, corroborates this finding.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recently, in vitro experiments using a neural cell line demonstrated that nesfatin-1 stimulates the phosphorylation of MAPK (19), CREBP (20), and AMPK (11), playing important roles in regulating feeding behavior and energy metabolism in vivo (12,13,(16)(17)(18)22,23). Our in vivo finding that the ICV injection of nesfatin-1 concentration dependently increased MAPK activity (phosphorylation of ERK1/2), but not AMPK, PI3K, or CREBP activity, corroborates this finding.…”
Section: Discussionsupporting
confidence: 81%
“…Although a receptor specific to nesfatin-1 has not yet been identified, the different signaling systems mediated by nesfatin-1 have been clarified. Nesfatin-1 stimulates the phosphorylation of mitogen-activated protein kinase (MAPK) (19), CREBP (20), and AMPK (11). However, the precise signaling mechanisms underlying nesfatin-1-induced activation of the sympathetic nervous tones in the brain remain to be determined.…”
mentioning
confidence: 99%
“…On the other hand, in this study, we demonstrated significant phosphorylation of mTOR following nesfatin-1 treatment in Ishikawa endometrial cancer cells. Similarly, nesfatin-1 is reported to decrease ERK 1/2 phosphorylation and exert anti-proliferative effects on H295R adrenocortical carcinoma cells [20], while it is also reported that NUCB2 is a positive mediator of EGF-stimulated ERK phosphorylation [33]. It is therefore suggested that the biological function of NUCB2 may vary among tissues, and further examinations are therefore needed to clarify the molecular mechanism associated with the diverse roles of NUCB2.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was estimated by XTT cell proliferation assay kit [6] following manufacture's instruction (Roche Applied Science, Tokyo, Japan). Briefly seeded cells were mixed with prepared 2,3-Bis (2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carbox-anilide (XTT) working solution for 6 h at 37 °C under 5% CO 2 and absorbance value was obtained at 490 nm with a reference correction at 630 nm.…”
Section: Cell Proliferation Assay By Xttmentioning
confidence: 99%